Importance of global communication to combat global pandemics: Lessons from the HIV Online Provider Education programme - Efeose A. Airewele; Henry Sunpath; Mahomed-Yunus S. Moosa; Rajesh T. Gandhi (AOSIS, 2021)
In many ways, the coronavirus disease 2019 (COVID-19) pandemic mirrors the challenges, lessons and opportunities of the HIV pandemic. In this article, we argue that global pandemics such as COVID-19 and HIV require a global response. We highlight the HIV Online Provider Education (HOPE) programme as an example of the importance of global communication when combating a pandemic. From both the COVID-19 and HIV pandemics, we have learned that to optimise health worldwide, it is necessary to have effective and efficient means of swiftly sharing experiences, expertise, best practices and guidelines. To prepare for the next public health emergency, clinicians and researchers must put in place and promote effective programmes for global communication.